Study of the Influence of Factors Determining the Results of Geophysical Surveys in Territories Contaminated with Light Non-Aqueous Phase Liquid - Mingaleva Tatiana; Shakuro Sergey; Egorov Alexey (Russian Journal of Earth Sciences)
To solve environmental problems in the search for hydrocarbon pollution, geophysics is often used. In contaminated sites, knowledge of the geological structure and hydrogeological conditions, as well as the qualitative and quantitative characteristics of pollution, is essential for risk assessment and site remediation planning. The article discusses the influence of various factors on the formation of anomalies detected by methods of shallow geophysics in the process of studying the pollution of the geological environment with oil products. The main purpose of such work is the detection, contouring and determination of the migration routes of light oil products. Understanding the processes occurring in the subsurface space during the distribution of oil products helps to correctly compare the variations in physical properties identified from geophysical data and the location of contaminated areas. One of the main factors affecting the results of geophysical surveys is the residence time of oil products in soils. The nature of geophysical anomalies changes and is a response from a complex multifactorial environment. Also, among the factors affecting the nature of geophysical anomalies, the following can be distinguished: the activity of microorganisms, redox reactions, the presence of near-surface heterogeneities, temperature, signal shredding, humidity and composition of soils in the aeration zone, fluctuations in the level of groundwater, the concentration of hydrocarbons, source of petroleum products. The paper also describes several generalized models of the distribution of hydrocarbon pollution, each of which can be used to solve the tasks set, and also be a useful tool for predicting the distribution of oil products and modeling geophysical responses from a multifactorial environment. At present, the most popular model is the “natural source zone depletion”, according to which methanogenesis plays an important role in technogenically polluted territories, as a result of which gases in anomalous concentrations are released from areas where hydrocarbons are processed by microorganisms as secondary waste products of bacteria. The authors also consider a model that is more typical for objects located on the banks of rivers or lakes. Here, the distribution model of light oil products is subdivided into three zones (donor zone, transit zone, and secondary accumulation zone), in which the processes of distribution and accumulation of oil products take place. Thus, a comprehensive study of the processes occurring in soils during oil spills and the use of theoretical models of pollutant migration can facilitate the work on the ecological study of soils contaminated with oil products.